2002
DOI: 10.1016/s0990-7440(01)01148-2
|View full text |Cite
|
Sign up to set email alerts
|

Is fertility of hybrids enough to conclude that the two oysters Crassostrea gigas and Crassostrea angulata are the same species?

Abstract: The distinction of the two cupped oysters Crassostrea gigas (Thunberg, 1793) and Crassostrea angulata (Lamark, 1819) into two species was chiefly due to their differing geographical distributions, C. gigas being present in Asia and C. angulata in Europe. Today it is commonly accepted that C. angulata and C. gigas are a single species according to morphological, genetic and F1 hybridization data. However, the demonstration of the fertility of their hybrids and the absence of any reproductive isolation remained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…Although a number of oyster breeders have conducted interspecific hybridization among the Crassostrea genus Batista et al, 2007Batista et al, , 2008Gaffney and Allen, 1993;Huo et al, 2013;Huvet et al, 2002Huvet et al, , 2004Piferrer et al, 2009;Xu et al, 2009Xu et al, , 2014Zhang et al, 2012Zhang et al, , 2014, there are no reports of further utilization of the hybrids with the exception of two subspecies of C. gigas and C. angulata (Wang et al, 2008). This is the first report to describe completely fertile backcrossed progeny and F 2 hybrids; this finding differed from the F 1 hybrids (C. hongkongensis ♀ × C. gigas ♂) that exhibited high levels of sterility .…”
Section: Restoration Of Progeny Fertilitymentioning
confidence: 74%
“…Although a number of oyster breeders have conducted interspecific hybridization among the Crassostrea genus Batista et al, 2007Batista et al, , 2008Gaffney and Allen, 1993;Huo et al, 2013;Huvet et al, 2002Huvet et al, , 2004Piferrer et al, 2009;Xu et al, 2009Xu et al, , 2014Zhang et al, 2012Zhang et al, , 2014, there are no reports of further utilization of the hybrids with the exception of two subspecies of C. gigas and C. angulata (Wang et al, 2008). This is the first report to describe completely fertile backcrossed progeny and F 2 hybrids; this finding differed from the F 1 hybrids (C. hongkongensis ♀ × C. gigas ♂) that exhibited high levels of sterility .…”
Section: Restoration Of Progeny Fertilitymentioning
confidence: 74%
“…4 Infection causing gill disease also reported from Crassostrea angulata (Lamarck) but C. gigas and C. angulata are now considered to be the same species based on morphological, genetic and progeny hybridization data (Huvet et al 2002). Characteristic gill disease was also reported in Mytilus edulis trossulus (Gould) from the Baltic Sea near Gdansk, Poland, but the causative agent was not identifi ed (Smolarz et al 2006).…”
Section: Lymnaea Truncatulamentioning
confidence: 99%
“…Both Aa and aA crosses were able to generate individuals with mature gametes, and their sex ratios were similar to those of the pure species (Table 2). Similarly, Huvet et al (2002) found that progeny of C. gigas and C. angulata crosses were able to produce mature gametes.…”
Section: Discussionmentioning
confidence: 85%